METODE ISTIQRA' DALAM PENETAPAN HUKUM ISLAM - Mashudi Mashudi (Isti`dal : Jurnal Studi Hukum Islam, 2014)
This paper is going to discuss how the istiqra method actually is in the establishment of Islamic law and how its application especially in the determination of the law in the contemporary era demanding more empirical arguments. The results are the istiqra method has some principles; First, the argument's collectivity in the application of a law, is not only with one argument, either the universal or the particular. Second, the principle of observing qarain al-ahwal (indications of certain circumstances), either manqulah, which is associated with the texts directly such as the principles of Islamic law, or ghairu manqulah, which is not directly related to the texts, but rather related to the context of the community. This allows istiqra to penetrate issue of both specific laws (far'iyah) and contemporary though. Third, not only doesistiqra', particular, Islamic law, contemporaryistiqra approach rely on bayani methods towards text, especially one textalone, but also uses watching the growing context. Tulisan ini hendak membahas bagaimana sebenarnya metode istiqra' dalam penetapan hukum Islam serta bagaimana cara penerapannya terutama dalam penetapan hukum di era kontemporer yang lebih menuntut argumen-argumen empirik. Hasil yang didapat bahwa metode istiqra' memiliki beberapa prinsip; Pertama, kolektifitas dalil dalam penerapan suatu hukum, bukan hanya dengan satu dalil saja, baik yang sifatnya universal maupun partikular. Kedua, prinsip memerhatikan qarain al-ahwal (indikasi-indikasi keadaan tertentu), baik manqulah, yakni yang berhubungan dengan nash-nash secara langsung seperti kaidah-kaidah hukum Islam, maupun ghairu manqulah, yaitu yang tidak berkaitan secara langsung dengan nash, melainkan berhubungan dengan konteks masyarakat. Hal ini memungkinkan Istiqra' menembus persoalan hukum-hukum spesifik (far'iyah) dan kontemporer sekalipun. Ketiga, pendekatan istiqra' bukan hanya mengandalkan metode bayani atas nash, apalagi satu nash saja, melainkan pemanfaatan pencermatan konteks yang berkembang.